Issues of the legal concept on the mechanism for controlling the proliferation of weapons of mass destruction and their financing - Arenova, L.K.; Sultanbekova, G.B. (KU publ., 2020)
The scientific development of the problem of organizing activities to counter the financing of the proliferation of weapons of mass destruction in the Republic of Kazakhstan requires the development of a legal concept for a mechanism for controlling the proliferation of weapons of mass destruction and its financing, which will logically determine the countermeasures strategy, where the prevention of merging with international terrorism and extremism occupies a special place. The relevance of the article reflects the real need for the insurance of national security, for the society, and for the financial and political system of the state to prevent the emergence of a threat, to finance the proliferation of weapons of mass destruction and their merging with international terrorism and extremism, legal forces and means. Emphasizing relevance, especially in the current period of time when the world is under quarantine associated with the COVID-19 pandemic, we believe that it is necessary to dwell in more detail on the forms of terrorist attacks. Such a form of terrorist attack as biological terrorism encompasses the use of biological weapons, which can be an artificially created new form of life, as well as the deliberately concealed use and use of various biological agents and toxins, mutations of bacteria and viruses. It should be noted that in the course of scientific research, the author's contribution of each project participant to its implementation will be strictly formalized. All results obtained will be formalized and divided in accordance with the current civil legislation of the Republic of Kazakhstan in the field of intellectual property.
Жаппай қырып-жою қарудың таралуын жəне оны қаржыландыру бақылау тетігі бойынша құқықтық тұжырымдама мəселелері
Вопросы правовой концепции по механизму контроля за распространением оружия массового уничтожения и его финансированию
Keywords: legal concept; financing of weapons of mass destruction; identifying and suppressing the financing of terrorism; biological terrorism; chemical attacks; biological attacks; pathogens; effective measures to counter the financing of terrorism and WMD; terrorist financing risks and WMD; terrorist organizations and groups; terrorists; exploitation of natural resources; payment products and services